Worldview, Social Consolidation, Science: Dialectic Relationship - Kyzym Mykola O.; Doronina Maya S. (Problemi Ekonomiki, 2019)
In Ukraine, the problem of social consolidation, the current state of which does not allow for a meaningful forecasting of its future, is getting more urgent. Many publications propose recommendations for solving this problem through a permanent diagnosing of mechanisms for the formation and development of worldview resources. The world around a person is continuously and abruptly changing and requires developing scientifically based mechanisms for conscious adapting of a person to it. The aim of the article is generalizing the prerequisites for the creation of theoretical and methodological support for harmonizing the development of a worldview, social consolidation and science in Ukraine. Worldview creates for a person a general view of the outside world he/she is guided by when making important decisions and committing acts of social significance. Studying worldview allows determining what social patterns should be built in Ukraine, how to organize the constructive discussion of the way of solving the current problems by people with different worldviews; will help adapt the system of dialectical principles that are traditionally used by scientists in Ukraine to studying worldview. The article presents the definitions of the basic categories of the topic under study, the attention being focused on the dependence of the worldview orientations and the model of behavior of a person, first of all, on his/her financial standing. Solving complex tasks set by the internal development of our society and the international situation puts forward a pressing issue of forming a systematized scientific worldview. Tackling problems of worldview of a society can be facilitated by revision of the concepts of building its scientific and educational spheres. Worldview management should be oriented not towards standard functions and principles of management but towards the formation of conditions for enhancing internal conscious sources of people’s desire to carry out their own unique ideas in practice. The processes of consolidation and solidarity are implemented both in society as a whole and its scientific sphere, in particular. They are manifested in their full in schools of thought.